Effects of Pluchea indica Less Leaf Extract and Chlorine to Hematological Profiles of Broiler Chickens - Febrianta , Harvey; Yunianto, Vitus Dwi; Sukamto, Bambang (International Journal of Poultry Science, 2015)
Pluchea indica Less is one of the medicinal plants which can be used as a natural feed additive to improve poultry production, especially broilers, while chlorine is used to inhibit bacteria growth. The purpose of this study was to assess and evaluate the effect of Pluchea indica Less leaf extract and chlorine to the hematological profile of broilers. The experimental design applied in this study was completely randomized design (CRD) with 5 treatments and 4 replications. The treatments were as follows T0: Basal feed without adding Pluchea indica Less leaf extract and chlorine; T1: Basal feed + 2% Pluchea indica Less leaf extract + 30 ppm chlorine; T2: Basal feed + 4% Pluchea indica Less leaf extract + 20 ppm chlorine; T3: Basal feed + 6% Pluchea indica Less leaf extract + 10 ppm chlorine; T4: Basal feed + 8% Pluchea indica Less leaf extract + 0 ppm chlorine. Data were analyzed using analysis of variance (ANOVA) at the level of 95%, when the result was significant, means were separated by Duncan’s multiple range tests. The values were considered significant if P